Genetically Encoding an Electrophilic Amino Acid for Protein Stapling and Covalent Binding to Native Receptors - Chen, Xiao-Hua; Xiang, Zheng; Hu, Ying S; Lacey, Vanessa K; Cang, Hu; Wang, Lei (ACS chemical biology, 2014)
Covalent bonds can be generated within and between proteins by an unnatural amino acid (Uaa) reacting with a natural residue through proximity-enabled bioreactivity. Until now, Uaas have been developed to react mainly with cysteine in proteins. Here we genetically encoded an electrophilic Uaa capable of reacting with histidine and lysine, thereby expanding the diversity of target proteins and the scope of the proximity-enabled protein cross-linking technology. In addition to efficient cross-linking of proteins inter- and intramolecularly, this Uaa permits direct stapling of a protein α-helix in a recombinant manner and covalent binding of native membrane receptors in live cells. The target diversity, recombinant stapling, and covalent targeting of endogenous proteins enabled by this versatile Uaa should prove valuable in developing novel research tools, biological diagnostics, and therapeutics by exploiting covalent protein linkages for specificity, irreversibility, and stability.